Conocimientos, comunicación, actitudes y prejuicios acerca de la sexualidad y el VIH- SIDA en alumnos del 4º y 5º año de educación secundaria del colegio “Fe y Alegría” la Era, Lurigancho Chosica, 2011 - Rafael Alfaro, Guísela (2019)
The aim of the study was to determine the levels of knowledge, communication level, level attitudes and level prejudices about sexuality and HIV-AIDS, students in the fourth and fifth year of secondary school “Fe y Alegria” No.41 the It was, Lurigancho 2011. The type of study was quantitative, descriptive, transversal. The study populationconsisted of a total of 204 students, ranging in age from 14 to 18 years. We used a data collection instrument, whichwas the “Scale Sexuality Information Management HIV-AIDS”, this instrument was validated by Quiroga andEgoavil (2000). The results obtained in relation to the level of knowledge about sexuality and HIV-AIDS were the53.1% is indifferent Regarding communication about sexuality and HIV-AIDS, 56.8% are indifferent. Level attitudes, it was found that 28.4% have a casual attitude about sexuality and HIV-AIDS. Also as to the level of 39.5% biasis indifferent. Concluding that students are indifferent to the knowledge, communication, attitudes and prejudicesabout sexuality and HIV-AIDS.